The Seven Sins of Memory: How the Mind Forgets and Remembers - Schacter, Daniel L. (Houghton Mifflin, 2001)
A groundbreaking work by one of the world's foremost memory experts, THE SEVEN SINS OF MEMORY offers the first framework that explains common memory vices -- and their surprising virtues. In this intriguing study, Daniel L. Schacter explores the memory miscues that occur in everyday life: absent-mindedness, transience, blocking, misattribution, suggestibility, bias, and persistence. Schacter illustrates these concepts with vivid examples -- case studies, literary excerpts, experimental evidence, and accounts of highly visible news events such as the O.J. Simpson verdict, Bill Clinton's grand jury testimony, and the search for the Oklahoma City bomber. He also delves into striking new scientific research, giving us a glimpse of the fascinating neurology of memory. Together, the stories and the scientific results provide a new look at our brains and at what we more generally think of as our minds.The sin of transience -- The sin of absent-mindedness -- The sin of blocking -- The sin of misattribution -- The sin of suggestibility -- The sin of bias -- The sin of persistence -- The seven sins: vices or attributes.
Keywords: Memory; Memory disorders; Recollection (Psychology).